Syringomyelia presenting with unilateral optic neuropathy: a case report - Ngoo, Qi Zhe; Tai, Evelyn Li Min; Wan Hitam, Wan Hazabbah (Dove Medical Press, 2017)
Purpose: In this case report, we present two cases of syringomyelia with optic neuropathy. Findings: In Case 1, a 36-year-old Malay lady presented to our clinic with acute onset of blurring of vision in her left eye that she experienced since past 1 month. She was diagnosed with syringomyelia 12 years ago and was on conservative management. Her visual acuity was 6/6 in the right eye and counting fingers at 1 m in the left. There was a positive relative afferent pupillary defect in her left eye. Optic nerve functions of her left eye were reduced. Visual field showed a left inferior field defect. Her extraocular muscle movements were full. Magnetic resonance imaging of the brain and spine showed syringomyelia at the level of C2–C6 and T2–T9. Both of her optic nerves were normal. Her condition improved with intravenous and oral corticosteroids. In Case 2, a 44-year-old Malay lady presented to our clinic with a progressive central scotoma in her right eye that she experienced since past 1 month. She had previous history of recurrent episodes of weakness in both of her lower limbs from past 8 months. Visual acuity in her right and left eye was 6/9 and 6/6, respectively. The relative afferent pupillary defect in her right eye was positive. Optic nerve functions of her right eye were affected. Visual field showed a central scotoma in her right eye. Her extraocular muscle movements were full. Fundoscopy of her right eye showed a pale optic disc. Her left eye fundus was normal. Magnetic resonance imaging of the brain and spine showed syringomyelia at T3–T6. Both of her optic nerves were normal. A diagnosis of syringomyelia with right optic atrophy was performed. Her condition improved with intravenous and oral corticosteroids. Conclusion: Optic neuropathy is a rare neuro-ophthalmic manifestation in patients with syringomyelia. Prompt diagnosis and timely management are essential to avoid a poor visual outcome. Intravenous corticosteroids are beneficial in the treatment of early optic neuropathy in syringomyelia.